Chinese rural poverty: marginalized or dispersed? - Riskin, Carl (American Economic Review, 1994)
Imagine two models of rural poverty distribution. One (which might be called the model) pictures the poor as confined to poverty regions of great natural adversity, separate and apart from regions. In the normal areas, on the other hand, there might be growing inequality, but there is little or no absolute poverty. The second model (the socioeconomic model) sees poor, rich, and middle class physically interspersed or living in proximity to one another. Which of these models more closely approximates reality is an important question. It affects the visibility of extremes of wealth and poverty, which is a politically sensitive matter. Also, characteristics of antipoverty policy will be very different according to whether it is necessary to identify and treat individual households and neighborhoods widely scattered among the nonpoor population or whether it is possible to target entire poor regions. In China, the ecological model is official